Present status of the functional advanced micro-, nano-printings – a mini review. (September 2020) - Mondal, K.; McMurtrey, M.D.
Abstract: Additive printing technology and expertise have experienced noteworthy development driven by their ability to revolutionize academic and industrial manufacturing and research. They also have particular practical uses in the areas of micro and nanofabrication. Micro- and nano-printings have found a tremendous number of applications in material synthesis/patterning, electronics, medicine and biotechnology. In this mini review, we examine the important additive micro and nano printing techniques, including contact and noncontact, and roll to roll (R2R) printing methods as well as recently emerging techniques such as micro- or nano-pen printings, laser-induced forward transfer (LIFT) and aerosol jet printing (APJ). We also discuss the materials that are printable by these technologies, the applications of micro- and nano-printings, key features, advantages and challenges. Graphical abstract: Image 1 Highlights: Established and emerging additive micro and nano-printing techniques were discussed. Contact, non-contact, roll to roll (R2R), as well as laser-induced forward transfer (LIFT) and aerosol jet printing (APJ) were reviewed. Applications, printable ink materials, key features, and their advantages and challenges of printings were also described.